Pemanfaatan Minyak Jelantah sebagai Bahan Dasar Sabun Cair di PT. Hasta Panca Mandiri Utama Site OBI - Panuntun, Muhammad Bagus; Samuel, Elfinza Brillian (Riviera Publishing, 2025)
This study aims to explore the utilization of waste cooking oil (minyak jelantah) as a base for liquid soap production at PT. Hasta Panca Mandiri Utama Job Site OBI. Typically disposed of as waste, waste cooking oil can be processed into liquid soap through hydrolysis and saponification using Potassium Hydroxide (KOH) as an alkaline agent. This research uses a descriptive method, conducted at PT. Hasta Panca Mandiri Utama Job Site OBI. The results show that waste cooking oil, after being filtered and mixed with other ingredients, can be converted into liquid soap suitable for hand washing. This process can help reduce the negative environmental impact of waste oil while providing an eco-friendly and cost-effective soap alternative for the company. The study is expected to raise awareness about the importance of managing waste cooking oil in the company and the surrounding community.